IFFs and Commodity Trading: Opportunities for Identifying Risks in Energy Traders' Financial Conduct Using Groups' Corporate Filings - Anastasia Nesvetailova; Ronen Palan; Hannah Petersen; Richard Phillips (City, University of London, City Political Economy Research Centre (CITYPERC), 2021)
The 'corporation' (or 'company' in English jurisprudence or 'societé' in French law) is a legal person that owns assets and partakes in contracts in markets. The 'multinational corporation,' otherwise known as 'transnational corporation' or the 'multinational enterprise' (MNE) is a group, an organization engaged in coordinating business activities by a variety of other entities, usually corporations. The MNE is not a legal person, and hence it does not own things or partake in contracts. Towards the end of the 20th century, the typical MNE, including the majority of the important global players in the energy trading sector, has evolved into highly complex, multisubsidiary, multi-jurisdictional organization, often spanning hundreds, if not thousands, of independent corporate entities, linked together by a complex web of ownership arrangements. Managers control the corporation on behalf of the firm. Despite common assumptions of this hierarchical relationship, they are not, in fact, the agents of shareholders but officers of the corporation. Considering that managers are officers of the corporations and not the agents of shareholders, throughout recent history of the rise of MNEs, suppliers of finance to the corporation had to make sure that managers do not steal the capital they supply, do not waste it on bad projects and more broadly, get managers to return some of the profits to them. Gradually, countries began to introduce rules, laws and regulations that were aimed to safeguard the rights of investors in these entities. A complex and sophisticated system of corporate governance, including reporting of financial activities by the group as a whole and by each of the corporate entity under its control has emerged as ways by which suppliers of finance to corporations assure themselves of getting a return on their investment. (...)
Keywords: 330